Análise dos efeitos do albedo no microclima de cânions urbanos - Gonzalez, Dominique Elena Giordano (2015)
Urban canyons, i.e. urban structures formed by a street flanked continuously by buildings, are responsible for their own microclimate, which is very diverse from the microclimate conditions found in open fields. Several factors contribute to typical conditions of the energy balance of street canyons. Among them are the geometry and orientation of the street canyon, and the material properties of its surfaces. The albedo, or reflectance, is a material property that indicates the surface capacity to reflect the incident solar radiation. Therefore, albedo is directly related to the surfaces' capacity to absorb energy or to reflect it to adjacent surfaces, and thus, can affect outdoor thermal comfort conditions. Nevertheless, the impact of albedo modifications is dependent on the available solar radiation gains, and on its magnitude compared to other factors affecting the energy balance, for instance, wind conditions. Understanding how such factors interact may subsidize urban design, providing more amenable outdoor comfort conditions, which therefore will promote an increase in the use of public spaces. Beyond thermal comfort implications, the understanding of urban microclimatic relations can bring improvements to other relevant issues, such as building energy demand, urban sustainability and Urban Heat Island effects. This research investigated the influence of albedo changes in urban canyon surfaces on the resulting microclimate. Results showed that the albedo effect on surface temperatures is limited by the solar exposure conditions of the surfaces. It was verified that the effect on air temperature is small, and that an increase of surface albedo tends to worsen thermal comfort conditions at the pedestrian level. Therefore, the adoption of high albedo should not be prescribed to canyon surfaces indiscriminately, as it requires an assessment of local conditions in order to identify which surfaces have enough solar exposure for an effective use of higher albedo. Benefits from albedo modifications should be considered alongside the improvement of urban thermal comfort conditions.